Inference of hyperedges and overlapping communities in hypergraphs - Martina Contisciani; Federico Battiston; Caterina De Bacco (Nature Communications, 2022)
Networks with higher-order interactions are known to provide better representation of real networked systems. Here the authors introduce a framework based on statistical inference to detect overlapping communities and predict hyperedges of any size in hypergraphs.